Modeling trophic webs in freshwater fishpond systems using Ecopath: towards better polyculture management - Aubin, J (2021)
Freshwater pond polyculture faces many challenges in Europe. Appropriate tools must be developed to better understand and manage trophic interactions in pond ecosystems. The objective of our study was to understand the trophic interactions and make inference on the fish diet in common carp polyculture through a combination of experiments and trophic web modeling. We conducted an experiment in small fishponds of common carp polyculture reared with roach and perch and used Ecopath with Ecosim software to characterize the food web. Two replicates of 3 treatments were performed: a semi-extensive pond with low fish density and no formulated feed, an intensive pond with twice the fish density and formulated feed and an intensive pond coupled with a planted lagoon. Ten trophic groups were defined to describe the food web. The modeling procedure enabled us to estimate the diets of each trophic group. The fish diet in fed and non-fed treatments differed greatly since the carp fed mainly on formulated feed when available. The roach exhibited trophic plasticity by adapting their diet to the available resources. The benthic macroinvertebrates and zooplankton were preyed upon intensively; they became the limiting factors for fish production and depended on phytoplankton availability. Detritus and phytoplankton were the main sources of nutrients in all treatments but were not used efficiently. These results provide several insights for improving polyculture. In particular, they promote better management of zooplankton and macroinvertebrates as food sources for target species and a better balance in fish assemblages for more efficient use of resources.